Temperature dependence of the electrical resistivity in quasicrystals. - Akbari-Moghanjoughi, Massoud. (University of Ottawa (Canada), 1995)
The applicability of the weak-localization theory to highly ordered quasicrystals raises the question of whether or not the long-range order in these alloys can be reconciled with the electronic disorder. This study did not detect any unusual structure-induced contribution to the resistivity at low temperatures other than those known for metallic glasses. The temperature dependence of the resistivity in icosahedral quasicrystals of high structural quality showed that the transport behaviour of these alloys at low temperatures can be satisfactorily explained in terms of conventional weak-localization and electron-electron interaction theories. The temperature dependence of the resistivity in weakly disordered (low-resistivity) alloys can be explained qualitatively in terms of the classical theories extended to liquids and disordered alloys. The experimental evidence shows the existence of a close relationship between the icosahedral quasicrystalline structure and the weak localization tendency of the electronic states at the Fermi level. To explain the temperature dependence of the resistivity at high temperatures additional models based on the concept of the band transition and hopping have to be invoked. In the high-resistivity stable icosahedral Al-Cu-Ru alloy the insulating-like (electron hopping) behaviour was found to dominate the electron transport even at low temperatures. This causes the deviations from the weak-localization theory and is due to the enhancement of the density of localized electronic states at the Fermi level. Consequently, the Anderson localization is collapsed in the vicinity of the metal-insulator transition. The values of the correlation gap in the Al-Cu-Fe-Mn icosahedral system suggest a considerably different nature for the pseudogap around the Fermi level in amorphous and icosahedral phases. However, unless an ideal quasicrystal belongs to the metal-insulator transition region (if it exists), the weak-localization theory will be the most appropriate tool to investigate the low temperature electron transport properties in icosahedral phases.
Keywords: Physics, Electricity and Magnetism.